Acute Care Nurses' Spiritual Care Practices. (June 2013) - Gallison, Barry S.; Xu, Yan; Jurgens, Corrine Y.; Boyle, Suzanne M.
The purpose of this study was to identify barriers in providing spiritual care to hospitalized patients. A convenience sample ( N = 271) was recruited at an academic medical center in New York City for an exploratory, descriptive questionnaire. The Spiritual Care Practice (SCP) questionnaire assesses spiritual care practices and perceived barriers to spiritual care. The SCP determines the percentage that provides spiritual support and perceived barriers inhibiting spiritual care. The participation rate was 44.3% ( N = 120). Most (61%) scored less than the ideal mean on the SCP. Although 96% ( N = 114) believe addressing patients spiritual needs are within their role, nearly half (48%) report rarely participating in spiritual practices. The greatest perceived barriers were belief that patient's spirituality is private, insufficient time, difficulty distinguishing proselytizing from spiritual care, and difficulty meeting needs when spiritual beliefs were different from their own. Although nurses identify themselves as spiritual, results indicate spirituality assessments are inadequate. Addressing barriers will provide nurses opportunities to address spirituality. Education is warranted to improve nurses' awareness of the diversity of our society to better meet the spiritual needs of patients. Understanding these needs provide the nurse with opportunities to address spirituality and connect desires with actions to strengthen communication and the nurse–patient relationship.